O ensino remoto emergencial na educação superior: o REDE na Universidade Federal de Santa Maria - Barbosa, Carolina Corrêa Gressler (2022)
This research was rolled-out through the Programa de Pós-Graduação em Educação at Universidade Federal de Santa Maria (UFSM). Our focus was to understand how the pedagogical activities were carried out considering the emergency teaching approaches developed in higher education during the Coronavirus pandemic. Our research problem is: considering the pandemic situation and its emergency teaching demands in higher education, which were the main pedagogical issues in activities carried out by professors. Our work was based in several authors and studies, such as Creswell e Clark (2002), Bolzan (2002, 2006, 2012, 2016, 2019, 2021), Cunha (2009, 2011, 2018), Gati (2011), Gil (1999), Marconi e Lakatos (2003),Isaia (2005, 2012), Kenski (2012), Moran (2015), Marcelo y Vaillant (2018), Nóvoa (2020), Powaczuk (2012), Tardif (2014). Our study uses qualitative and quantitative approachs, based on a survey including multiple choice itens and free-text comments. This survey was sent to bachelor course professors at UFSM. All of them were evolved in emergency teach strategy developed by UFSM, which was called Regime de Exercícios Domiciliares (REDE). We analyzed survey results, pointing out categorial dimensions, pedagogical activities and emerging contexts. These elements are interrelated in the professor learning process, having emergency teaching as a transverse background axis. In this scenario, specially at REDE, we identified the following emerging contexts: working time and spaces; boundaries and challenging situation faced of; technological fluence; internet quality and availability; student indifference and unengagement. Putting all together, we can point out that professors had to reorganize their pedagogical activities, which made it possible for us to understand the way these changes can occur beyond the traditional classroom environment and impact in the pedagogical activities. We also focused our analysis in bachelor courses, so this is another limitation. In the future, new researches evolving some more universities or focusing on some other course degrees can be carried out to get a deeper knowledge about the theme.